New Oxford textbook of psychiatry - Gelder, Michael G. (Oxford University Press, 2012)
The award winning 'New Oxford Textbook of Psychiatry' is one of the leading reference works in this field. Bringing together over 200 chapters from the leading figures in the discipline, it presents a comprehensive account of clinical psychiatry, with reference to its scientific basis and to the patient's perspective throughout